2022
DOI: 10.1111/jfpp.16720
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of peppermint polyphenols within crystalline sucrose matrix: Fortification of gummy candy as a food model system

Abstract: In this study, the phenolic extract of peppermint was loaded within a sucrose matrix at three concentrations (3%, 5%, and 10%) by the co‐crystallization process. Physical properties (flowability, color indices, density, solubility, and hygroscopicity), total phenolic content (TPC), and antioxidant properties (DPPH*, ABTS+, OH* radicals scavenging activity, and reducing power) and morphology of the samples were evaluated. The co‐crystallized powders (Co‐10%) were substituted with sucrose at different levels (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…In another study, Suman et al [ 78 ] showed a similar trend for GCs enriched with 1–6% ginger powder, 0.02–0.14% ginger oleoresin, and 5–30% ginger juice. In addition, Sarabandi and Mohammadi [ 79 ] evaluated the possible use of peppermint extracts in GCs and assessed their physical properties, total phenolic content (TPC), and antioxidant properties. The GC containing 10% peppermint extract exhibited the highest antioxidant capacity in various assays, making it a suitable antioxidant agent in the formulation of functional GCs with desirable texture, antioxidant, and sensory properties.…”
Section: Development Of Gcs As a Functional Foodmentioning
confidence: 99%
“…In another study, Suman et al [ 78 ] showed a similar trend for GCs enriched with 1–6% ginger powder, 0.02–0.14% ginger oleoresin, and 5–30% ginger juice. In addition, Sarabandi and Mohammadi [ 79 ] evaluated the possible use of peppermint extracts in GCs and assessed their physical properties, total phenolic content (TPC), and antioxidant properties. The GC containing 10% peppermint extract exhibited the highest antioxidant capacity in various assays, making it a suitable antioxidant agent in the formulation of functional GCs with desirable texture, antioxidant, and sensory properties.…”
Section: Development Of Gcs As a Functional Foodmentioning
confidence: 99%
“…Co-crystals of phenolic or carotenoid extracts fall under the first category. Examples include extracts of banana pulp and peel [11], green tea [12], butterfly pea flower [13], brasella rubra [8], propolis [14], carrot [15], aronia [16], mint polyphenols [17], and pomegranate peel [18]. Pure substances such as glucose [6,19], fructose [19], combinations of glucose and fructose [19], magnesium sulfate and calcium lactate [20,21], zinc sulfate [22], curcumin [23], vitamin B12 [24], soluble fiber [25], and catechin hydrate and curcumin [26] are included in the second group.…”
Section: Introductionmentioning
confidence: 99%